PENGARUH GAYA KEPEMIMPINAN, KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DI PT PUPUK INDONESIA (PERSERO) - Agus; Adella Rohma Daniar (Pasca Sarjana Universitas Satya Negara Indonesia, 2015)
This study is aimed to analyze and assess the influence of leadership style, competence and organizational commitment to employee performance Fertilizer Indonesia PT (Persero). This research is a quantitative study with explanatory survey methods and data collection tools used questionnaires. The results of this study concluded that the style of leadership, competence and organizational commitment to employee performance Fertilizer Indonesia PT (Persero), either jointly or individually, where the value of the correlation coefficient kepemimpianan style (X1), competence (X2) and organizational commitment (X3) on the performance of employees is 0,791, that means style kepemimpianan (X 1), competence (X2) and organizational commitment (X3) has a strong relationship to employee performance and test results determinant coefficient (R2) obtained the value of 0.625 which can disimpulakan style kepemimpianan(X1), competence (X2) and organizational commitment (X3) gives a contribution of 62.50%, against an increase in the performance of employees, while the remaining 37.50% is influenced by other factors not examined in this study.